Bio-intensive gardening (BIG) in grades IV, V, and VI, public elementary schools of Banayoyo-Lidlidda-San Emilio and Burgos-San Esteban Districts, Ilocos Sur - Gallardo, Berting P. (Sta. Maria, Ilocos Sur : [s.n.], 2012)
This study aimed to determine the status of the Bio-Intensive Gardening (BIG) Program instruction in the public elementary schools of Banayoyo- Lidlidda- San Emilioand Burgos- San Esteban Districts, Ilocos Sur during the school year 2011-2012.
Bibliography: pages 61-62.
CHED-La Union
Keywords: Gardening